The Use of Mind Mapping to Teach Reading Comprehension - Sopian Saori (Journal of Languages and Language Teaching, 2020)
The research was aimed at finding out the impact of using mind mapping toward students’ reading comprehension. This study was classified as a quasi experimental research design using two intact classes as an experimental and control group. The experimental group was treated using mind-mapping technique, while the control group was subjected to conventional learning technique. The sample of this study was the first year students of Nabi’ Nubu’ Islamic Senior High School. The instrument of this study employed reading test for students in both groups. The reading tests were distributed in the pre-test and post-test. The data analysis used descriptive and inferential statistic. The data were met the normal and homogeneous data. The result of the study showed that the mean scores of the experimental group (71.76) was higher than the control group (60.24) after treatment was given. Thus, the use of mind mapping has a significant effect towards students’ reading comprehension. It indicated that the technique can be an alternative technique to teach reading comprehension.